CRISPs Function to Boost Sperm Power Output and Motility - Gaikwad, Avinash S.; Nandagiri, Ashwin; Potter, David L.; Nosrati, Reza; O’Connor, Anne E.; Jadhav, Sameer; Soria, Julio; Prabhakar, Ranganathan; O’Bryan, Moira K. (Frontiers in Cell and Developmental Biology, 2021)
Fertilization requires sperm to travel long distances through the complex environment of the female reproductive tract. Despite the strong association between poor motility and infertility, the kinetics of sperm tail movement and the role individual proteins play in this process is poorly understood. Here, we use a high spatiotemporal sperm imaging system and an analysis protocol to define the role of CRISPs in the mechanobiology of sperm function. Each of CRISP1, CRISP2 and CRISP4 is required to optimize sperm flagellum waveform. Each plays an autonomous role in defining beat frequency, flexibility and power dissipation. We thus posit that the expansion of the CRISP family from one member in basal vertebrates, to three in most mammals, and four in numerous rodents, represents an example of neofunctionalization wherein proteins with a common core function, boosting power output, have evolved to optimise different aspects of sperm tail performance.